2023
DOI: 10.1177/15459683221147006
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Aerobic Exercise on Motor Sequence Learning and Corticomotor Excitability in People With Parkinson’s Disease

Abstract: Background People with Parkinson’s disease (PD) are known to have motor learning difficulties. Although numerous studies have demonstrated that a single bout of aerobic exercise (AEX) can facilitate motor learning in non-disabled adults, the same beneficial effect in PD is unknown. Furthermore, associated neuroplastic changes have not been investigated. Objectives This study aimed to determine whether a single bout of aerobic exercise (AEX) can facilitate motor sequence learning in people with PD and to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
2
1
Order By: Relevance
“…The differing results in the current study may relate to the use of high-intensity exercise, and a more cognitively complex motor task. The current findings also contrast with preliminary findings in clinical populations such as Parkinson’s disease, wherein exercise was found to have no impact on motor acquisition during serial reaction time 36 and whole-body balance tasks 35 , 36 . Notably these studies also utilised moderate intensity exercise protocols, rather than high-intensity as in the current study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The differing results in the current study may relate to the use of high-intensity exercise, and a more cognitively complex motor task. The current findings also contrast with preliminary findings in clinical populations such as Parkinson’s disease, wherein exercise was found to have no impact on motor acquisition during serial reaction time 36 and whole-body balance tasks 35 , 36 . Notably these studies also utilised moderate intensity exercise protocols, rather than high-intensity as in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…This may relate to the cascade of neurochemical changes induced by high-intensity exercise, which may maintain an interval environment favourable for memory consolidation, including increased circulation of catecholamines 69 , lactate 70 , and brain-derived neurotrophic factor (BDNF) 71 . Notably, studies involving participants with Parkinson’s disease have shown motor learning improvements following moderate intensity exercise 35 , 36 . Individuals with age-related neurodegenerative disorders may demonstrate benefits from exercise on motor learning at a lower intensity compared to healthy older adults, due to the impact of exercise on disease related processes 72 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation